Dangerous reef aquaristics: Palytoxin of a brown encrusting anemone causes toxic corneal reactions. (November 2015) - Ruiz, Yasmin; Fuchs, Joan; Beuschel, Ralf; Tschopp, Markus; Goldblum, David
Abstract: Although frequently observed in domestic saltwater aquariums, literature on exposure to palytoxin (PTX) of encrusting anemones (Zoanthidea) kept in aquariums is rare. Handling these animals for propagation purposes or during cleaning work can lead to dermal, ocular or respiratory contact with the PTX generated by some Zoanthids. The present study describes a case of ocular exposure to liquid from a Zoanthid, which led to corneal ulcers. The patient also suffered from systemic symptoms of dyspnea and shivering and a suspected rhabdomyolysis, which required monitoring in the Intensive Care Unit. After symptomatic treatment provided insufficient results, the corneal ulcers improved with an amniotic membrane transplantation. A review of the literature regarding ocular exposures to this diverse order of Hexacorallia reveals that severe and systemic symptoms can develop with minimal contact. Graphical abstract: Highlights: Literature on exposure to palytoxin of anemones kept in aquariums is rare. Ocular contact with an anemone's fluid caused a toxic local and systemic reaction. Severe corneal ulcers developed. Corneal ulcers were successfully treated with amniotic membrane transplantation.